Representasi Perdagangan Manusia Dalam Film “Cross The Line” (Analisis Roland Barthez) - Akhmad Ibnu Fadhilla; Priatna (Tamilis Synex: Multidimensional Collaboration, 2024)
Movies function as mass media that represent reality in society. For example, the issue of human trafficking that often occurs is told in the movie "Cross the Line" (2022). In this study, the movie "Cross the Line" is used as a subject to look for representations of human trafficking. This research uses predetermined theories to find the meaning of signs in several scenes of the movie. Using Roland Barthes' semiological model, data analysis was conducted through three stages of signification: denotation, connotation, and myth. This research concludes that: (1) Denotation in the film is shown with human trafficking behavior through manipulation representation, slavery representation, representation of doing anything to get money, smuggling representation. This is reflected in the harsh background and storyline of the movie, depicting life on the ship. (2) Connotation is characterized in the film by real human trafficking in society, where the poor are always positioned as helpless and become victims of human trafficking. (3) Myth is characterized in the film by the fact that the representation of human trafficking is formed by social inequality in Indonesia.